The Associations between Depressive Symptoms and Self-Rated Health in Relation to Sense of Coherence among Adolescents: Cross-Sectional Study - Vilija Malinauskiene; Romualdas Malinauskas (MDPI AG, 2024)
Background: We investigated the predictors of poor SRH in a representative sample of Lithuanian mainstream school students in grades 7-8. We also checked for gender differences in the associations between SRH and depressive symptoms and other predictors. Methods: A total of 2104 7th-8th-grade students participated (response rate 73.95%) and were asked about depressive symptoms, psychosomatic health complaints, negative acts at school, feeling at school, family stress and violence, sense of coherence, self-esteem, and lifestyle. We used a hierarchical regression analysis including a variety of self-rated health predictors. Results: Boys scored significantly higher on physical activity and smoking, whereas girls scored significantly higher on SRH, depressive symptoms, psychosomatic health complaints, and family stress and violence, though the significance was lost in the hierarchical regression. Depressive symptoms were the strongest predictor of poor SRH (standardized β = 0.309, p < 0.001), though other investigated predictors were also significant but had lower effect sizes. Strong evidence was found supporting the buffering role of sense of coherence in the relationship between depressive symptoms and SRH (standardized β = −0.266, p < 0.001). Conclusions: We can conclude that the magnitude of the relationship between depressive symptoms and self-rated health is dependent on the levels of sense of coherence. We did not find gender differences in those associations. As poor SRH is easy to determine, especially with a one-item question, the cases of poorly rated health should be detected early and corrected by interventions in order to prevent poor health outcomes in the future.